Persepsi Petani terhadap Penerapan Inovasi Pengelolaan Tanaman Terpadu Padi Sawah Tadah Hujan di kabupaten Jayapura, Papua - Petrus A Beding (Jurnal Ilmiah Inovasi, 2018)
AbstractThe approach of agricultural development cannot be separated from the role of technological innovation. As an innovation, the process of adopting the Innovation Technology of rainfed lowland rice requires a process of understanding (perception) by the farmers. An innovation will be adopted by farmers if they have a good perception of the innovation. Therefore, the purpose of this study will examine how the perception of farmers on the application of innovation PTT rainfed lowland rice. This research was conducted in Kampung Benyom Jaya 1 Nimbokrang District Jayapura Regency, Papua was conducted from May to September 2017 in Kampung Benyom Jaya 1 Nimbokrang District, Jayapura District. The method used in this research is the descriptive method. The determination of respondents was conducted by the census to farmers who participated in rain-fed rice paddy technology training. then measured by using theÂ  Likert scale. The results showed that farmers perceptions of the application of technological innovation are quite good this includes positive criteria. If farmers have a good perception is expected to adopt the innovative technology of rainfed lowland rice can run quickly.Â Keywords: Perception, Farmer, Innovation, rice, rainfed rice field